Perancangan Sistem Manajemen Surat Berbasis Web Pada Kantor Camat Tano Tombangan Angkola - Indah Purnama Sari; Oris Krianto Sulaiman; Fanny Ramadhani; Andy Satria (INCODING: Journal of Informatics and Computer Science Engineering, 2023)
In the process of administrative modernization, it is necessary to implement an information system that can support all administrative activities in an institution, institution or company. At the Tano Tombangan Angkola District sub-district office, South Tapanuli, there is still a conventional letter archive management method where archive recording is still done using books and stationery. This often causes many problems, such as lost documents, damage or unrecorded documents. In this research, the authors try to develop an application that can record all archives in the agency. Then it will be stored in the database and can be accessed anytime and anywhere. As a result, many benefits are provided to agencies, such as more structured and neat archival data collection. The management system created in this paper is Web-based using PHP.